2013
DOI: 10.1038/ncomms3063
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric control of frozen state in a toroidal glass

Abstract: The glass state of matter represents a frozen state of an atomically disordered system with local order only. Instead of atoms, systems with glassy states of magnetic and electric dipole moments in solids are known as spin and dipole glasses, respectively. In these conventional glasses, slow dynamics, such as relaxation and memory phenomena, are characteristics of their magnetic/dielectric properties. Here we propose a new glassy state in solids, a 'toroidal glass', in which toroidal moments-vector-like electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Today, the range of static toroidal systems under study includes various compounds 34,35 , boracites 36 , pyroxines 37 and olivines 38 , metals 39 , glasses 40 , ferroelectric nanoscale disks and rods 27 , molecular magnets 41,42 . However, unambiguous observations of long-range toroidal order have proven challenging due to the weak, short-range interactions between toroidal dipoles and the requirement of simultaneously breaking both space and time reversal symmetry to demonstrate its existence 18 .…”
Section: Static Toroidal Multipolesmentioning
confidence: 99%
“…Today, the range of static toroidal systems under study includes various compounds 34,35 , boracites 36 , pyroxines 37 and olivines 38 , metals 39 , glasses 40 , ferroelectric nanoscale disks and rods 27 , molecular magnets 41,42 . However, unambiguous observations of long-range toroidal order have proven challenging due to the weak, short-range interactions between toroidal dipoles and the requirement of simultaneously breaking both space and time reversal symmetry to demonstrate its existence 18 .…”
Section: Static Toroidal Multipolesmentioning
confidence: 99%
“…They used a simple Landau free energy argument to show how the magnetoelectric effect arises. However, doping with even a small amount of Ni 2+ into the Mn 2+ site substantially changes both the magnetic and electrical properties of the system [18,20,22], which complicates the mechanism for magnetoelectric behaviour.…”
Section: -Introductionmentioning
confidence: 99%
“…[15] But, over the last eight years MnTiO3 has once again been the subject of scientific scrutiny for its strong magnetoelectric properties. [16][17][18][19][20][21][22] Mufti et al [16] showed that the application of electric and magnetic fields along the c-axis results in a strong dielectric anomaly and pyroelectric current up until the spin flop transition. They used a simple Landau free energy argument to show how the magnetoelectric effect arises.…”
Section: -Introductionmentioning
confidence: 99%
“…For the ilmenite structure of the XY-like spin glass Ni x Mn 1−x TiO 3 (x ≈ 0.42), the Ni 2+ and Mn 2+ ions are randomly distributed in the magnetic (Ni, Mn) plane and form a honey comb lattice. At the presence of the cross-product of the electric and magnetic field components, a net toroidal moment is polarized in the direction perpendicular to the honeycomb lattices during the spin-freezing process (in Figure 2B) [81].…”
Section: Toroidization and Me In Materialsmentioning
confidence: 99%
“…A static toroidal moment exists in various materials both microscopically and macroscopically, covering transition metal ions [68], biological and chemical macromolecules [69][70][71][72][73][74], bulk crystals [75][76][77][78][79][80], and glasses [81]. In macroscopic condensed matter, formation of toroidal moments in materials plays a vital role in the asymmetric ME.…”
Section: Toroidization and Me In Materialsmentioning
confidence: 99%